Editorial for the Special Issue on Micromachined Acoustic Transducers for Audio-Frequency Range - Libor Rufer; Shubham Shubham; Haoran Wang; Tom Miller; Petr Honzík; Vittorio Ferrari (Micromachines)
Microelectromechanical systems (MEMS) refer to miniaturized mechanical and electro-mechanical elements that are fabricated through microelectronic processes [...]